2011
DOI: 10.2337/dc10-1364
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Abdominal Visceral and Subcutaneous Adipose Tissue and Metabolic Syndrome in a Korean Population

Abstract: OBJECTIVEThis study aimed to assess the correlation between abdominal subcutaneous adipose tissue (SAT) and metabolic syndrome (MetS) in Korean adults after adjusting for the effects of visceral adipose tissue (VAT).RESEARCH DESIGN AND METHODSThe SAT/VAT ratio (SVR) was calculated using abdominal computed tomography in 2,655 subjects. We used regression analyses to assess whether the SVR predicted MetS.RESULTSFor both sexes, the prevalence of elevated triglycerides, reduced HDL, and elevated fasting glucose si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 15 publications
3
45
1
Order By: Relevance
“…Recently, Gesta et al showed for the first time that glypican-4 is differentially expressed in visceral and sc adipose tissue in humans, which suggests that glypican-4 might play an important role in body fat distribution and in functional differences between visceral and sc adipose tissue (3). Because the absolute quantification of any given fat deposit does not reflect its relative distribution, the VFA/SFA ratio has been suggested as an effective measurement of body fat distribution (11). Recently, Kaess et al demonstrated that in the Framingham Heart Study cohort, the VFA/SFA ratio was significantly correlated with metabolic risk factors even after adjusting for BMI and visceral adipose tissue, suggesting that the propensity to store fat viscerally vs sc might be a unique risk factor independent of absolute fat volumes (12).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gesta et al showed for the first time that glypican-4 is differentially expressed in visceral and sc adipose tissue in humans, which suggests that glypican-4 might play an important role in body fat distribution and in functional differences between visceral and sc adipose tissue (3). Because the absolute quantification of any given fat deposit does not reflect its relative distribution, the VFA/SFA ratio has been suggested as an effective measurement of body fat distribution (11). Recently, Kaess et al demonstrated that in the Framingham Heart Study cohort, the VFA/SFA ratio was significantly correlated with metabolic risk factors even after adjusting for BMI and visceral adipose tissue, suggesting that the propensity to store fat viscerally vs sc might be a unique risk factor independent of absolute fat volumes (12).…”
Section: Discussionmentioning
confidence: 99%
“…This shift in fat stores of the body from subcutaneous to visceral depots may be reflected by a high VAT volume/SAT volume ratio. The VAT/SAT ratio has been associated with CVD and metabolic risk, beyond BMI or VAT alone (2,3,5,18,19). Thus, the goals of our study were (1) to examine whether increases in SAT density were associated with a propensity to store fat viscerally vs subcutaneously and (2) to test whether high fat density and a high VAT/SAT ratio are jointly associated with an increased burden of CVD risk factors.…”
mentioning
confidence: 97%
“…Regional fat depots may confer differential cardiovascular disease (CVD) risk, with visceral adipose tissue (VAT) volume more closely associated with CVD risk factors than subcutaneous adipose tissue (SAT) volume (1). A large body of work has shown that VAT is associated with increased insulin resistance, type 2 diabetes, metabolic syndrome, and the atherogenic lipoprotein profile (2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…In particular, visceral fat is strongly associated with MetS [31,32]; however, the association with subcutaneous fat is still controversial [33]. A recent Korean study showed that abdominal subcutaneous fat was inversely correlated with the occurrence of MetS after adjustment for visceral fat [34]. An MNT or lifestyle change program is one of the most well-known strategies to reduce body fat [35]; however, the mechanism of action of these programs and the direct effects on adipose tissue are not well defined.…”
Section: Discussionmentioning
confidence: 99%